2012
DOI: 10.1121/1.4728169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deafness on acoustic characteristics of American English tense/lax vowels in maternal speech to infants

Abstract: Recent studies have demonstrated that mothers exaggerate phonetic properties of infant-directed (ID) speech. However, these studies focused on a single acoustic dimension (frequency), whereas speech sounds are composed of multiple acoustic cues. Moreover, little is known about how mothers adjust phonetic properties of speech to children with hearing loss. This study examined mothers' production of frequency and duration cues to the American English tense/lax vowel contrast in speech to profoundly deaf (N ¼ 14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 57 publications
4
33
0
Order By: Relevance
“…Recent studies have presented contradictory results on the degree of vowel space expansion in ID speech to populations both with and without hearing impairment (Cristia & Seidl, 2014;Englund & Behne, 2006;Kondaurova et al, 2012;C. Lam & Kitamura, 2010, 2012.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have presented contradictory results on the degree of vowel space expansion in ID speech to populations both with and without hearing impairment (Cristia & Seidl, 2014;Englund & Behne, 2006;Kondaurova et al, 2012;C. Lam & Kitamura, 2010, 2012.…”
mentioning
confidence: 99%
“…Several studies have demonstrated no enhancement of the distance between vowel categories and/or expansion of the acoustic vowel space area in speech to children with normal hearing compared with AD speech (Cristia & Seidl, 2014;Englund & Behne, 2006). Although evidence of vowel space expansion exists when a talker is aware that an adult listener has a hearing impairment (Ferguson & Kewley-Port, 2002;Picheny, Durlach, & Braida, 1986), partial or no vowel space expansion was observed in speech to children with hearing impairment (Kondaurova et al, 2012;C. Lam & Kitamura, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This agrees with previous literature that shows maternal speech to HI infants is affected by infant hearing loss (Chen, 1996;Cheskin, 1981;Cross, JohnsonMorris, & Nienhuys, 1980;Kondaurova & Bergeson, 2011;Kondaurova et al, 2012;Kondaurova, Bergeson, & Kitamura, 2013;Kondaurova, Bergeson, & Xu, 2013;Kondaurova et al, 2015;Kondaurova, Blank, Zheng, Abu Zhaya, & Seidl, 2016;Nienhuys, Cross, & Horsborough, 1984;Wieland, Burnham, Kondaurova, Bergeson, & Dilley, 2015). Previous research has demonstrated that mothers use shorter utterances, exaggerated pitch characteristics, and a slower speaking rate when interacting with their HI infants (Kondaurova, Bergeson, & Xu, 2013).…”
Section: Infant and Mother Vocalizationssupporting
confidence: 82%